Multiplicative Valency-Based Descriptors for Silicon Carbides Si2C3 − I[p, q], Si2C3 − II[p, q], Si2C3 − III[p, q], and SiC3 − III[p, q] in Drug Applications. (8th June 2020) - Xu, Jin; Javaid, Nasir; Bilal, Shamas; Rafaqat, Muhammad; Tlili, Iskander
Abstract : Topological indices help us to collect information about algebraic graphs and give us a mathematical approach to understand the properties of algebraic structures. In literature, there are more than 148 topological indices, but none of them can completely describe all properties of chemical compounds. Together, they do it to some extent, so there is always room to define new topological indices. In this paper, we introduced the multiplicative version of Shingali and Kanabour indices and computed these indices for Silicon Carbides Si 2 C 3 − I p, q, Si 2 C 3 − II p, q, Si 2 C 3 − III p, q, and SiC 3 − III p, q .